Nitrogen Availability and Use Efficiency in Wheat Crop as Influenced by the Organic-Input Quality Under Major Integrated Nutrient Management Systems - Bhardwaj, Ajay K.; Rajwar, Deepika; Yadav, Rajender K.; Chaudhari, Suresh K.; Sharma, Dinesh K. (Frontiers in Plant Science, 2021)
Purpose: One of the serious constraints for the integration of organics in soil fertility plans is the release and availability of nitrogen (N) to match the critical growth stages of a crop. The interplay between organic amendment characteristics and soil moisture conditions can significantly affect the nutrient release and availability. In this study, the effects of integrated nutrient management strategies using diverse qualities of organic amendments on daily N mineralization and its availability to plants during the full growing season of the wheat crop were analyzed in a 10-year long experiment. Methods: The management included: 1) F=inorganic fertilizers at 100% rate, compared to a reduced rate of inorganic fertilizers (55% N) supplemented with organic inputs via2) GM=green manuring, 3) LE=legume cropping and its biomass recycling, 4) WS=wheat stubble retention, 5) RS=rice stubble retention, and 6) FYM=farmyard manure application, during the preceding rice season. Ion exchange resin (IER) membrane strips were used as plant root simulators to determine daily NH4+-N and NO3--N availability in soil solution during the full wheat growing period. Results: Total available N for the full season was in the following order: GM (962 µg cm-2)>F (878 µg cm-2) >LE (872 µg cm-2)>FYM (865 µg cm-2)>RS (687 µg cm-2)>WS (649 µg cm-2). No significant differences were observed in NH4+-N availability throughout the cropping period as compared to NO3--N which showed significant differences among management at critical crop growth stages. Conclusions: Legume biomass incorporation (GM, LE) and farmyard manure (FYM) based management provided the most consistent supply equivalent to or even exceeding 100% inorganic fertilizers at several critical stages of growth, especially at tillering and stem elongation. Integration of organics in management increased nitrogen use efficiency 1.3-2.0 times, with cereal crop residue based management having highest efficiency followed by legume biomass incorporation.